Upaya meningkatkan motivasi dan kinerja guru - Supriadi Supriadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
In order to carry out their duties and responsibilities, a teacher is required to have certain abilities and skills. These abilities and skills are part of the teacher's professional competence. To make the teacher as a professional, it is necessary to carry out continuous and continuous coaching, and to make the teacher a workforce that needs to be considered, valued and recognized for professionalism. Teacher performance will be good if the teacher has done the elements that consist of loyalty and high commitment to the task of teaching, mastering and developing learning materials, discipline in teaching and other assignments, creativity in teaching, collaboration with all school members, leadership that student role models, good personality, honest and objective in guiding students, and responsibility for their duties. In addition to performance, the motivation of teachers to carry out their duties and responsibilities is also important for efforts to improve the learning process that will improve the quality of graduates in the school. This research is a school action research subject of 12 teachers. This study consisted of two cycles. The results of the study show that the supervision of the principal can increase teacher motivation and performance in SD Negeri 04 Talaok, District of Bayang, South Coastal District.